Recent Updates on the Role of the MicroRNA-10 Family in Gynecological Malignancies. (19th December 2022) - Li, Chunhua; Zhu, Xiangling; Lv, Xinyue; Han, Xintong; Xu, Yuting; Huang, Jinhua; Chen, Xiaochun; Yu, Zhiying
Abstract : The ever-increasing morbidity associated with gynecological malignancies constantly endangers the physical and psychological health of women. Since a long time, there has been an urgent need for a deeper understanding of the tumorigenesis and the development of gynecological cancer to identify new molecular markers for early diagnosis and metastatic disease prognosis and for the development of therapeutic targets. MicroRNAs are crucial cellular regulators. The microRNA-10 (miR-10) family has been found to play an integral role in the evolution of numerous cancer types. A comprehensive understanding of current studies on miR-10 could provide better insights into future research and clinical applications in related fields. This article reviews the latest research on the role of the miR-10 family in gynecological malignancies and the relevant molecular mechanism, mainly focusing on endometrial, cervical, and ovarian cancers.